What's Missing? Anti-Racist Sex Education! - Whitten, Amanda (Université d'Ottawa | University of Ottawa, 2011)
Contemporary sexual health curricula in Canada include information about sexual diversity and queer identities, but what remains missing is an explicit discussion of anti-racist sex education. Although there is official federal and provincial support for multicilturalism and anti-racism in schools, contemporary Canadian sex education omits crucial anti-racist work and foundational anti-racist education frameworks are silent on sex curriculum. Although anti-racism should be infused into all school curricula, sex education represents an especially vital subject for anti-racist education, for sex and sexuality have been racialized in a variety of ways. As sexual health topics are increasingly added into health and physical education curricula across Canada, it is vital to appraise their contents critically. This lack of attention paid to race, racism and racialization leads to the appearance of a raceless sex education and this ''racelessness'' -a reinforcing of whiteness and white bodies as the standard -is what I am investigating in Ontario and Canada sex education government documents. In order to show the ways that racism and racialization work to produce a raceless sex education, I employ a content analysis based on a key word search of Ontario public secondary school health provincial curricula and the federal sex education policy. Public School curricula were selected based on their sexual health content. English language curricula were selected from Ontario and Canada to maximize the congruency of politics and country of origin. All documents examined were created within the same nine-year range (1999-2008) to maximize similarity in social climate surrounding the documents. Two health and physical education curricula from Ontario were selected as a sample of public school curricula, one of the Grade 9/10 curricula and one of the Grade 11/12 curricula. One set of federal sexual health guidelines, the most recent version of the Canadian Guidelines for Sexual Health Education (2008), was selected as a sample of government policy devoted to sex education. This content analysis provides the basis for anti-racist sex education policy recommendations organized around three vital objectives to be infused into existing Ontario public school sex education curriculum. As anti-racism critically examines the education institution and sexual health curricula are an increasingly politicized example of potentially transformative education, anti-racism must be incorporated into sex education.